Answer:
[tex]a=\frac{2S -2v_ot-2s_o}{t^2}[/tex]
Step-by-step explanation:
We have the equation of the position of the object
[tex]S = \frac{1}{2}at ^2 + v_ot+s_o[/tex]
We need to solve the equation for the variable a
[tex]S = \frac{1}{2}at ^2 + v_ot+s_o[/tex]
Subtract [tex]s_0[/tex] and [tex]v_0t[/tex] on both sides of the equality
[tex]S -v_ot-s_o = \frac{1}{2}at ^2 + v_ot+s_o - v_ot- s_o[/tex]
[tex]S -v_ot-s_o = \frac{1}{2}at ^2[/tex]
multiply by 2 on both sides of equality
[tex]2S -2v_ot-2s_o = 2*\frac{1}{2}at ^2[/tex]
[tex]2S -2v_ot-2s_o =at ^2[/tex]
Divide between [tex]t ^ 2[/tex] on both sides of the equation
[tex]\frac{2S -2v_ot-2s_o}{t^2} =a\frac{t^2}{t^2}[/tex]
Finally
[tex]a=\frac{2S -2v_ot-2s_o}{t^2}[/tex]